The potential of traditional Malay woodcarving as a cultural heritage tourism product in Kuala Terengganu / Wan Najihah Wan Nordin, Ahmad Nazrin Aris Anuar and Rohaslinda Ramele Ramli - Wan Nordin, Wan Najihah; Anuar, Ahmad Nazrin Aris; Ramli, Rohaslinda Ramele (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Cultural heritage includes both tangible and intangible assets. However, the growth of cultural heritage in the tourism industry has been focused on tangible assets. Furthermore, as an element in traditional craftsmanship, the craft is considered an intangible cultural heritage that has become a tourism product in a specific tourism area. This study was conducted to determine the potential of woodcarving as a cultural heritage tourism product in Kuala Terengganu. In this study, five respondents were selected using purposive sampling as an approach for data collection. According to the findings, Malay traditional craftsmanship has the potential to be marketed as a tourism product. In any case, several factors must be improved, such as i) the attraction, ii) destination facilities, iii) transportation, and iv) accessibility to the site to increase the viability of Malay traditional handicrafts as a popular tourism product in Kuala Terengganu. In conclusion, it will be advantageous to Malaysia's and other nations' tourism industries since traditional craftsmanship will be viewed as a new commodity in tourism. Furthermore, it can help preserve craftsmanship skills and knowledge. It can also encourage the next generation to learn about and respect this tradition.